Inflation in Developing Asia: Demand-Pull or Cost-Push? - Juthathip Jongwanich; Donghyun Park (Asian Development Bank (ADB), 2008)
This paper empirically examines the relative importance of different sources of inflation in developing Asia. In particular, it tests the widely held view that the region's current inflation surge is primarily the result of external price shocks such as oil and food shocks. In addition, this paper also estimates the degree of pass-through of external price shocks to domestic prices. Our central empirical result is that contrary to popular misconception, Asia's inflation is largely due to excess aggregate demand and inflation expectations rather than external price shocks. This suggests monetary policy will remain a powerful tool in the fight against inflation in Asia. Another significant finding is that the pass-through of the external price shocks to domestic prices has been limited so far. However, the removal of government subsidies is likely to lead to greater pass-through in the future. The resulting inflationary pressures provide a further rationale for tightening monetary policy.
hdl:11540/1780
Keywords: 330; Inflation; Asien